2011
DOI: 10.1038/srep00135
|View full text |Cite
|
Sign up to set email alerts
|

New Abundant Microbial Groups in Aquatic Hypersaline Environments

Abstract: We describe the microbiota of two hypersaline saltern ponds, one of intermediate salinity (19%) and a NaCl saturated crystallizer pond (37%) using pyrosequencing. The analyses of these metagenomes (nearly 784 Mb) reaffirmed the vast dominance of Haloquadratum walsbyi but also revealed novel, abundant and previously unsuspected microbial groups. We describe for the first time, a group of low GC Actinobacteria, related to freshwater Actinobacteria, abundant in low and intermediate salinities. Metagenomic assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
322
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(344 citation statements)
references
References 57 publications
18
322
2
2
Order By: Relevance
“…Even though the bacterial abundance was comparable to that typically described for high-salt environments (Demergasso et al, 2008;Baricz et al, 2014), the fact that they constituted~78% of the monimolimnion community was unanticipated, as previous studies reported the dominance of Archaea at salinities 4300 g l − 1 (Ghai et al, 2011;Baricz et al, 2014). We assume that the increased abundance of Bacteria in the deeper water strata could be achieved by outcompeting Archaea in suboxic hypersaline conditions, as the majority of halophilic archaeal species are aerobic (Andrei et al, 2012).…”
Section: Vertical Patterns In Prokaryotic Abundancesmentioning
confidence: 65%
“…Even though the bacterial abundance was comparable to that typically described for high-salt environments (Demergasso et al, 2008;Baricz et al, 2014), the fact that they constituted~78% of the monimolimnion community was unanticipated, as previous studies reported the dominance of Archaea at salinities 4300 g l − 1 (Ghai et al, 2011;Baricz et al, 2014). We assume that the increased abundance of Bacteria in the deeper water strata could be achieved by outcompeting Archaea in suboxic hypersaline conditions, as the majority of halophilic archaeal species are aerobic (Andrei et al, 2012).…”
Section: Vertical Patterns In Prokaryotic Abundancesmentioning
confidence: 65%
“…These advances led to the identification and genomic characterization of multiple novel high-rank archaeal lineages that have previously escaped detection in 16S ribosomal RNA (rRNA) gene-based diversity surveys because of their extremely low relative abundance, limited distribution or mismatches to archaeal 16S rRNA gene primer sequences (Baker et al, 2010;Nunoura et al, 2011;Narasingarao et al, 2012). These discoveries necessitated phylogenetic and phylogenomic-based reassessment of the taxonomic structure of the domain Archaea (Lake et al, 1984;BrochierArmanet et al, 2008;Elkins et al, 2008;Ghai et al, 2011;Guy and Ettema, 2011;Williams et al, 2012). The most recent and comprehensive phylogenomicsbased assessment of the domain Archaea (Rinke et al, 2013) combined data from 35 novel archaeal single amplified genomes (SAGs) with previously published archaeal genomes to propose a three archaeal superphyla scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The DPANN superphylum encompasses the 'Nanoarchaeota' (Waters et al, 2003;Podar et al, 2013), the only DPANN phylum with cultured representatives, as well as the candidate phyla 'Nanohaloarchaeota' (defined from metagenomic assembly (Narasingarao et al, 2012) and SAGs (Ghai et al, 2011) from hypersaline environments); 'Parvarchaeota' (defined from a metagenomic assembly from an acid mine drainage; Baker et al, 2010), 'Aenigmarchaeota' (defined from three SAGs from Homestake mine groundwater seep (Lead, SD, USA) and the Great Boiling Spring sediments; Rinke et al, 2013) and 'Diapherotrites' (defined from SAGs from Homestake mine groundwater seep; Rinke et al, 2013). As such, the DPANN superphylum represents an intriguing collection of phyla with disparate physiological preferences and environmental distribution, ranging from the obligatory symbiotic and thermophilic species within the 'Nanoarchaeota', to the acidophilic candidate phylum 'Parvarachaeota' and to the non-extremophilic candidate phyla 'Aenigmarchaeota' and 'Diapherotrites'.…”
Section: Introductionmentioning
confidence: 99%
“…Full random metagenome sequencing of multiple hypersaline systems (Santa Polasaltern in Spain -13 to 37% salinity), the hypersaline lake Tyrell in Australia (29% salinity) and crystallizer ponds in the USA (18 to 38% salinity) show equally high phylotypic diversity and the general dominance of Archaea, in particular the square-shaped halophilic archaeon Haloquadratum walsbyi [38][39][40][41]. Remarkably, de novo sequence assembly of metagenomic samples from hypersaline environments has led to the discovery of a novel uncultivated class, the "Nanohaloarchaea", previously detected only once by "classic" 16S rRNA amplicon sequencing [42] but now known to be dominant in these systems across the world [39,40]. De novo genome annotation has revealed the projected metabolic capacities of the uncultured Nanohaloarchaea with (i) a unique combination of protein amino acids to increase both osmo-resistance and protein flexibility, (ii) the first complete archaeal pentose-phosphate-pathway and (iii) the absence of Gvp gas vesicle protein orthologs which are otherwise highly conserved in halophilic archaeal genomes [40].…”
Section: Extremely Halophilic Habitatsmentioning
confidence: 99%
“…De novo genome annotation has revealed the projected metabolic capacities of the uncultured Nanohaloarchaea with (i) a unique combination of protein amino acids to increase both osmo-resistance and protein flexibility, (ii) the first complete archaeal pentose-phosphate-pathway and (iii) the absence of Gvp gas vesicle protein orthologs which are otherwise highly conserved in halophilic archaeal genomes [40]. Single-cell genomic analyses have further characterized a member of this euryarchaeal class as a low-GC photoheterotrophic, salt-in strategist with the ability to degrade polysaccharides [39].…”
Section: Extremely Halophilic Habitatsmentioning
confidence: 99%